Cooperative caching for homogeneous wireless sensor networks. (22nd June 2009) - Sharma, T.P.; Joshi, R.C.; Misra, Manoj
In many scenarios, data generated at sensor nodes in wireless sensor networks must be stored temporarily in a network for subsequent use. An individual sensor node's storage capacity is too small to hold it and may soon overflow. Therefore, we propose an effective caching strategy based on cooperation among various sensor nodes to form a larger cumulative cache. As part of the complete caching scheme, a novel token-based cache admission control scheme is devised, which ensures proximity of cached data closer to sink(s). A cache discovery mechanism to efficiently fetch a copy of data items is developed. A single-copy cache coherency scheme is developed to avoid sink from fetching stale data and also avoids undesired data replication. Further, a least utility based item-replacement policy is developed to evict data items with the least utility in case of desired replacement. Simulation results show significant improvements in network energy savings and data availability when cooperative caching is used.